The genetics of amyotrophic lateral sclerosis - Kenna, Kevin (Trinity College (Dublin, Ireland). Department of Genetics, 2013)
Amyotrophic lateral sclerosis, commonly referred to as motor neuron disease or simply ALS, is a neurological disorder which involves the degeneration of upper and lower motor neurons. The disease is associated with a progressive loss in voluntary muscle function and usually proves fatal within 3 years of symptomatic onset. There is no cure and the most effective therapy to date is believed to extend survival by only a few months. Multiple genetic causes have been identified but these account for only a minority of cases and in most instances disease onset cannot be explained. Furthermore, the true pathogenicity of many reported disease mutations has not been validated.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin